Critical HRD—A Mithridate?. (November 2014) - Hill, Bob
The Problem: Current crises such as the global financial meltdown, disparate distribution of income, growing economic inequalities, business and government complicity in favoring an economic elite, war on the middle class, and oppressive market behaviors have been linked to corporate and business practices, with little resistance from the academy, including the field of human resource development (HRD). In fact, HRD has been portrayed by some as collusive. Recent arguments suggest that critical HRD can recalibrate this equation. This article interrogates whether adding criticality to HRD can be an antidote to such complicity, that is, can it be a mithridate? The Solution: Rather than baptize HRD in the waters of criticality, where HRD remains the center of gravity with critical theory merely informing it, this article proposes that a transdisciplinary approach has the potential to offer more effective interventions in the current crises. Transdisciplinarity, the space between the disciplines of HRD and critical theory, may open up a unity of knowledge beyond the canonical borders of either field, yielding a new holism with important implications for practice. The Stakeholders: HR and OD professionals, adult educators, cultural critics.